West Syndrome: Report of Clinical Case: 9 Years of Follow-up - Claudia Akemi NACAMURA; Débora de Melo TRIZE; Lidia Regina Costalino CABELLO; Solange de Oliveira Braga FRANZOLIN; Sara Nader MARTA (Faculdade São Leopoldo Mandic, 2018)
West Syndrome is one of the rare and severe childhood epilepsies, starting in the first year of life and having an uncertain etiology. Even if some of the symptoms are missing, a triad of them defines West Syndrome, including epileptic spasms, arrest or regression of psychomotor development, and hypsarrhythmia on interictal electroencephalography. The objective of this study was to obtain updated data on West Syndrome literature and report a clinical case of a patient with the medical diagnosis of this syndrome, with gastrostomy feed tube, and clinical pattern of spastic quadriplegia. Initial clinical examination showed prolonged retention of deciduous teeth, periodontal disease, poor oral hygiene, mouth breathing, deep palate, anterior open bite, tongue interposition between the dental arches, and low caries experience. Over 9 years the patient presented complications in their sistemicas conditions, with need for gastrostomy and many periods of hospitalization that determined periods of absence for the dental monitoring. Despite this, currently his oral health condition is good and stable. Dental care for people with disabilities should be developed, encouraged and continuously extended, in agreement with the constitutional principles of human dignity and the rights for health and equality.